Further Steps Toward the Development of Gluten Reference Materials – Wheat Flours or Protein Isolates? - Schall, Eszter; Scherf, Katharina A.; Bugyi, Zsuzsanna; Török, Kitti; Koehler, Peter; Schoenlechner, Regine; Tömösközi, Sándor (Frontiers in Plant Science, 2020)
Celiac disease is a gluten-induced hypersensitivity reaction that requires a lifelong gluten-free diet. Gluten-free foods must not contain more than 20 mg/kg gluten as laid down by Codex Alimentarius. Measuring the presence of gluten with routine immunoanalytical methods in food is a serious challenge as many factors affect accurate determination. Comparability of the results obtained with different methods and method validation are hindered by the lack of a widely accepted reference material (RM). The core questions of RM development from wheat are the number of cultivars to be included and the format of gluten (i.e., flour, gluten, or gliadin isolates) to be applied. Therefore, the aim of our work was to produce an appropriate gluten RM from wheat. For this, five previously selected wheat cultivars and their blend were used to produce flours, gluten and gliadin isolates under laboratory conditions. Protein content, protein composition and responses to different ELISA methods were compared and widely evaluated in our study. The protein contents of the flours were 12.1–18.7%, those of the gluten isolates 93.8–97.4% and those of the gliadin isolates 72.7–101.9%. The gluten and gliadin isolates had similar protein profiles as the source flours. By comparing the different wheat cultivars and their protein isolates, we found that the isolation had a smaller effect on protein composition than genetic variability. The choice of a blend would be more suitable for the production of a RM in case of flours and also isolates. The immunoanalytical results showed that the isolation had an effect on the analytical results, but its extent depended on the ELISA method. The use of flour would be more applicable in this regard, but handling of the material and long-term stability should also be considered in the final decision of gluten RM production.